An evaluation of instructional management in four Dominican-managed diocesan schools in Davao del Norte - Damasco, Ma. Corazon B. (Animo Repository, 1994)
This study covers the comprehensive evaluation of the instructional management of the four Dominican-managed diocesan schools using Stufflebeam's Context-Input-Process-Product (CIPP) evaluation model. The study was conducted in the four Dominican-managed diocesan schools in Davao, namely: Maryknoll High School of Panabo, Maryknoll High School of Sto. Tomas, Maryknoll High School of Kapalong and Assumption Academy of Mawab. The sample of the study consisted of 74 teachers, 12 subject coordinators, 1 assistant principal, and 4 principals. This sample of 91 respondents represented 88 percent of the study population. Descriptive statistics such as frequencies, means, and standard deviations were used to present the respondents' profile and their evaluative responses. Qualitative data were content analyzed. Context evaluation findings revealed that the Mission Statements, goals and objectives of the four Dominican-managed Diocesan schools generally aim towards the integrated development of students. The respondent schools have no formal written document of their instructional management program. Input evaluation results revealed that majority of the respondent teachers (88 percent) completed a bachelor's degree and had an average teaching experience of 7.6 years. Thirty-three percent of subject area coordinators had master's units and had an average supervisory experience of 2.4 years. The instructional supervisors perceived their teachers as moderately committed in attaining the school's philosophy and objectives, aware of educational problems and professionally prepared to maintain discipline among students. As a whole, classroom facilities in the respondent schools were moderately pleasant and attractive, but provisions for facilities, equipment and supplies were very limited. Process evaluation showed that the main problems of the teachers were maintaining classroom discipline, inadequate instructional materials, and absence of post-observation feedback from instructional supervisors. Foremost problems of the instructional supervisors were: lack of funds to support faculty in-service training and remedial classes for students, and fast turnover of teachers. The teachers and instructional supervisors themselves perceived the latter's concern for effective instruction as moderate. The results of product evaluation showed that instructional objectives of the Dominican-Diocesan schools, teachers' teaching performance, student learning and curricula were moderately satisfied. The findings drew the following conclusions: 1. Instructional management of the respondent schools were congruent with the schools' Mission Statements, goals and objectives. 2. The human resources of the respondent schools, namely, the teachers and their instructional supervisors had adequate educational background and experience. However, material resources were inadequate and limited. 3. The problems of instructional management in the respondent schools were mostly due to financial constraints. 4. In spite of the problems and limitations that surfaced in the study it may be concluded that instructional management in the respondent schools had been moderately successful.